To pay, heal, and repair Mother Earth in the Sierra Nevada de Santa Marta: Experiences of indigenous women’s reparation in the implementation of the Colombian Peace Accord - Santamaria, Ángela (International review of victimology, 2023)
This paper describes collaborative research with Wiwa and Arhuaco women concerning local reparations with an intersectional perspective on the Colombian post-conflict agreement. Our central argument is that indigenous women’s processes, experiences, and expectations of reparation reflect a wish to engage in a dialogue with the Special Jurisdiction for Peace (JEP) through its Works, Projects or Activities (TOAR) so that their perspectives on and complex conceptions of harm and reparation, as well as their relationship with social orders, bodies, and territory, can be recognized and considered in managing the risks of the revitalization of patriarchy during the post-accord period.